An empirical investigation of software customization and its impact on the quality of software as a service: perspectives from software professionals - Ali, Abdulrazzaq Qasem; Md Sultan, Abu Bakar; Abd Ghani, Abdul Azim; Zulzalil, Hazura (Multidisciplinary Digital Publishing Institute, 2021)
Although customization plays a significant role in the provision of software as a service (SaaS), delivering a customizable SaaS application that reflects the tenant’s specific requirements with acceptable level of quality is a challenge. Drawing on a pr-developed software customization model for SaaS quality, two fundamental objectives of this study were to determine whether different software customization approaches have direct impacts on SaaS quality, and also to assess the construct reliability and construct validity of the model. A questionnaire-based survey was used to collect data from 244 software professionals with experience in SaaS development. Structural equation modeling was employed to test the construct reliability, construct validity, and research hypotheses. The measurement model assessment suggested that the six-construct model with 39 items exhibited good construct reliability and construct validity. The findings of the structural model assessment show that all customization approaches other than the integration approach significantly influence the quality of SaaS applications. The findings also indicate that both configuration and composition approaches have positive impacts on SaaS quality, while the impacts of the other approaches are negative. The empirical assessment and evaluation of this model, which features a rich set of information, provides considerable benefits to both researchers and practitioners.